Dewaxing and Post-Pretreatment Washing: Impact on Sugar and Ethanol Yields from Tobacco Residue - Muhammad Ayub Khan, Muhammad Ayub Khan; Panakkal, Elizabeth Jayex; Sriariyanun, Malinee; Gundupalli, Marttin Paulraj; Roddecha, Supacharee; Katam, Keerthi; Jayaprakash, Jayapriya; Cheenkachorn, Kraipat (Applied Science and Engineering Progress, 2024)
Waste generated from tobacco cultivation has negatively impacted the environment due to its inappropriate disposal methods. This negative impact can be mitigated by valorizing tobacco residue. In this study, tobacco residue was pretreated and the effect of dewaxing and washing on sugar and ethanol yields was studied. Tobacco residue was pretreated with alkali (2.17 M NaOH, 94 °C, 4.5 h) or acid (2.95 wt% H2SO4, 133 °C, 0.92 h). The effect of dewaxing was studied by incorporating the dewaxing step prior to pretreatment. Similarly, the effect of washing was analyzed by omitting post-pretreatment washing. Compositional analysis revealed that dewaxing prior to alkaline pretreatment improved cellulose content by 80% compared to the standard pretreated sample. Enzymatic hydrolysis of the samples showed that pretreatment had improved sugar yield by up to 6.1 times. Moreover, the sugar yield further improved when dewaxing and post-pretreatment washing steps were incorporated into the process. The unwashed biomass showed a 3-fold decrease in sugar compared to untreated biomass. Furthermore, fermentation studies showed that the dewaxed alkaline pretreated tobacco residue enhanced ethanol yield by 34% compared to standard pretreated biomass. Thus, this study reveals the potential of tobacco residue valorization and emphasizes the importance of dewaxing and post-pretreatment washing in a biorefinery.